2002
DOI: 10.1046/j.1365-2648.2002.02307.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical competence assessment in nursing: a systematic review of the literature

Abstract: The assessment of clinical competence remains almost universally accepted in the nurse education literature as a laudable pursuit yet there are aspects of it that remain at odds with the higher education of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
352
0
35

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(393 citation statements)
references
References 85 publications
6
352
0
35
Order By: Relevance
“…Watson et al, (2002) suggest that competence is a nebulous concept defined in deferent ways by different people. Its relationship with other concepts such as capability, performance, proficiency and expertise make it even more difficult to define.…”
Section: Introductionmentioning
confidence: 99%
“…Watson et al, (2002) suggest that competence is a nebulous concept defined in deferent ways by different people. Its relationship with other concepts such as capability, performance, proficiency and expertise make it even more difficult to define.…”
Section: Introductionmentioning
confidence: 99%
“…Watson et al indicated reliability (the degree to which an instrument measures consistently) and validity (the degree to which an instrument measures the construct) are basic topic in the use of measurement and should be applied strictly to the measurement of practice competence [26]. This study demonstrated the internal consistency and validity was acceptable and overall questionnaires possessed good internal consistency and reliability.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, the second domain in this study is "practice competence evaluation", Rubaish and Klein showed that the content of practice learning evaluations should possess the following characteristics: correlate with the program goals, an objective evaluation method, and content that attract student interest [24,25]. Watson et al also mentioned diverse of circumstances are created that obstruct the objective evaluation of students' performance [26]. Therefore, practice competence based evaluation could offer objective reference message to modify nursing curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…El trabajar desde el enfoque de competencias se constituye en una estrategia pedagógica, que lleva a potenciar tanto los procesos académicos como la formación del profesional 9 . Es por ello, que evaluar implica una visión global que incluye la mirada de los actores que intervienen.…”
Section: Discussionunclassified